2006
DOI: 10.1080/13573320600813440
|View full text |Cite
|
Sign up to set email alerts
|

Re-conceiving ability in physical education: a social analysis

Abstract: In this paper we explore how 'ability' is currently conceptualised in physical education and with what effects for different groups of young people. We interrogate approaches to theorizing ability in physical education that draw on sociological and phenomenological 'foundations' together with notions of ability as 'physical' and 'cultural capital' drawn from the work of Bourdieu. We also look to data we and others have collected across a number of empirical projects to ask: where do we find talk about what we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
74
0
8

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(83 citation statements)
references
References 14 publications
1
74
0
8
Order By: Relevance
“…Typical for the participants, Birgitte suggested that it entails "…making sure every pupil feels they are seen in your PE lesson, whatever their starting point." The complexities of 'who the pupil is', or indeed, the complexities of 'ability' (Evans, 2004;Wright & Burrows, 2006) and the organisational challenge of providing learning tasks which reflect the variation inevitably present in a group were not a part of their discourse.…”
Section: Physically Competent Performing Pe Teacher Selvesmentioning
confidence: 99%
“…Typical for the participants, Birgitte suggested that it entails "…making sure every pupil feels they are seen in your PE lesson, whatever their starting point." The complexities of 'who the pupil is', or indeed, the complexities of 'ability' (Evans, 2004;Wright & Burrows, 2006) and the organisational challenge of providing learning tasks which reflect the variation inevitably present in a group were not a part of their discourse.…”
Section: Physically Competent Performing Pe Teacher Selvesmentioning
confidence: 99%
“…Este poderoso proceso normativo comienza con la atracción de un determinado tipo de estudiante a los centros de formación en CCAFD (Brown, 2005;Brown & Evans, 2004;Brown & Rich, 2002;Rich, 2001;Wright, 2002): aquellas personas que han tenido una experiencia satisfactoria en los ámbitos del deporte y la EF porque reúnen los capitales físicos asociados a las formas hegemónicas de masculinidad, como son la capacidad para rendir en el deporte competición y la posesión de un físico atlético y musculoso (Wright & Burrows, 2006). Desarrollan así una identidad deportiva masculina que les predispone a entrar en el ámbito de los estudios de CCAFD y que a su vez les cualifica para ello (p.e., mediante la superación las pruebas físicas de acceso).…”
Section: Introductionunclassified
“…In the context of senior PE in Queensland, Hay and Macdonald (2010) highlighted the consensus amongst teachers was that males excel in terms of physical ability whilst females are more academically able. These assumptions have consequences for the ways in which males and females view and act within their social worlds (Wright & Burrows, 2006), and repercussions for the ways in which teachers identify ability and achievement (Hay & Macdonald, 2010).…”
Section: Developing the Sahpe: Insights From Literaturementioning
confidence: 99%
“…Fitzpatrick's (2011) work with Maori and Pacifica youth further highlights the need for enhanced understandings of HPE in particular cultural contexts, and how as a specialised field of knowledge it expresses and legitimates dominant culture and class hierarchies (Bernstein, 1990;2000). Wright and Burrows (2006) point us towards work by a range of authors who have provided valuable insights into the ways in which "physical 'ability' has been used to differentiate between different races and ethnicities" (p.286). They discuss the false dichotomisation of 'black bodies' (they include Maori, Pasifica, Australian Aboriginal and Afro-American bodies) and 'white bodies' with the former assumed to have physical ability, and the latter assumed to have intellectual ability.…”
Section: Developing the Sahpe: Insights From Literaturementioning
confidence: 99%